Answer:
1. -6
2. 35
3.-88
4. 12
hope it helps :)
Which expression is the simplest form of 3(2x + y) + 4(x - 4y) + x2?
Answer:
x^2 + 10x - 13y.
Step-by-step explanation:
3(2x + y) + 4(x - 4y) + x^2 First apply the Distributive law to the parentheses:
= 6x + 3y + 4x - 16y + x^2 Now add like terms:
= 10x - 13y + x^2.
Which expression is the simplest form of 3(2x+y)+4(x-4y)+[tex]x^{2}[/tex]?
Answer:
[tex]x^{2}[/tex]-13y+10x
Step-by-step explanation:
3(2x+y)+4(x-4y)+[tex]x^{2}[/tex]
6x+3y+4x-16y+[tex]x^{2}[/tex]
[tex]x^{2}[/tex]-13y+10x
Troy drew a triangle with coordinates ( 5 , 6 ) , ( 5 , 4 ) , and ( 8 , 4 ) . He rotated the triangle 180° about the origin. What are the coordinates of the image? Select all that apply.
A. (−5, 6)
B. (−5, −4)
C. (−5, −6)
D. (−8, −4)
i hate doing this but i really dont know the answer and im already failing :( please help
Answer:
The answers are B, C, and D.
Step-by-step explanation:
When you rotate an image 180° about the origin, you are flipping it twice. An easy rule is that an (x, y) pair becomes (-x, -y). Now just reverse the sign of the coordinates. Our rotated shape has the coordinates (-5, -6), (-5, -4), and (-8, -4).
Answer: C. (−5, −6) D. (−8, −4)
Step-by-step explanation:
We know that the rule for rotation a shape by [tex]180^{\circ}[/tex] (counterclockwise or clockwise) is given by :-
[tex](x,y)\to(-x,-y)[/tex] [Polarity of coordinates gets changed]
Given : Troy drew a triangle with coordinates ( 5 , 6 ) , ( 5 , 4 ) , and ( 8 , 4 ) . He rotated the triangle 180° about the origin.
Then, the coordinates of the image will be :-
[tex]( 5 , 6 )\to(-5,-6)[/tex]
[tex]( 5 , 4 )\to(-5,-4)[/tex]
[tex]( 8 , 4 )\to(-8,-4)[/tex]
From the options, the coordinates of the image = (-5,-6) and (-8, -4)
Hence, option C and D are correct.
3. Angle A in triangle ABC is obtuse. Can angle B or angle C be obtuse? Explain your reasoning
No, angle B or angle C can't be obtuse.
Step-by-step explanation:It is given that:
Angle A in triangle ABC is obtuse.
This means that:
∠A > 90°
Now, let us assume that:
Angle B is obtuse.
i.e. ∠B > 90°
Hence, we get that the sum of two angle is greater than 180 degree.(i.e. ∠A+∠B > 180° )
hence, the sum of all the three angles will be greater than 180 degrees.
But we know that in order to form a triangle the sum of all the three angles must be equal to 180 degree.
No, angle B and angle C cannot be obtuse if angle A is obtuse because the sum of angles in a triangle is always 180 degrees, and if one angle is obtuse, the other two must be acute to satisfy this rule.
We have,
In a triangle, the sum of all angles is always 180 degrees.
If angle A in triangle ABC is obtuse, it means it measures more than 90 degrees (greater than a right angle).
For the sum of the angles to be 180 degrees, angles B and C must be acute (measuring less than 90 degrees).
This is because if either angle B or angle C were obtuse, the sum of the angles would exceed 180 degrees, which is not possible in a triangle.
So, angle B and angle C cannot be obtuse if angle A is obtuse.
Thus,
No, angle B and angle C cannot be obtuse if angle A is obtuse because the sum of angles in a triangle is always 180 degrees, and if one angle is obtuse, the other two must be acute to satisfy this rule.
Learn more about triangles here:
https://brainly.com/question/25950519
#SPJ3
Polygon ABCD is translated to create polygon A'B'C'D'. Point A is located at (1,5) os located at (-2,1). What is the distance from B to B'?
Answer:
The distance from B to B' is 5 units
Step-by-step explanation:
The complete question is
Polygon ABCD is translated to create polygon A'B'C'D'. Point A is located at (1,5) and point A' is located at (-2,1). What is the distance from B to B'?
we know that
In a translation the figure maintains its dimensions and internal angles
so
AA'=BB'=CC'=DD'
The distance BB' is the same that the distance AA'
Find the distance AA'
the formula to calculate the distance between two points is equal to
[tex]d=\sqrt{(y2-y1)^{2}+(x2-x1)^{2}}[/tex]
we have
A(1,5),A'(-2,1)
substitute in the formula
[tex]AA'=\sqrt{(1-5)^{2}+(-2-1)^{2}}[/tex]
[tex]AA'=\sqrt{(-4)^{2}+(-3)^{2}}[/tex]
[tex]AA'=\sqrt{25}[/tex]
[tex]AA'=5\ units[/tex]
therefore
The distance from B to B' is 5 units
write 4.55 as a mixed number and as a improper fraction
Step-by-step explanation:
[tex]4.55-4\ and\ 55\ hundredths\\\\4.55=4\dfrac{55}{100}=4\dfrac{55:5}{100:5}=4\dfrac{11}{20}=\dfrac{(4)(20)+11}{20}=\dfrac{91}{20}[/tex]
[tex]4.\underbrace{55}_{2_{digits}}=4\dfrac{55}{1\underbrace{00}_{2_{zeros}}}[/tex]
Please answer this correctly
Answer:
Ashley
Step-by-step explanation:
William scored more than Riley
So William>Riley
Ashley scored fewer than Riley
So William>Riley>Ashley
Lauren scored more than William
So Lauren>William>Riley>Ashley
Where do I plot those fractions
Answer:
plot decimal values
Step-by-step explanation:
One approach is to convert them to decimal using your calculator or long division:
3/4 = 0.75
7/9 ≈ 0.78
1/2 = 0.50
2/3 ≈ 0.67
Since the number line has 0.1 increments, you can place each value in between the right increments. For instance 3/4 you place between 0.7 and 0.8. You place it halfway because 0.75 is halfway between 0.7 and 0.8. It's ok to estimate the exact location in this case.
Answer:
Step-by-step explanation:
What is the answer to x- (-12) = -3
help please!!!!;;;;;;;;;;;;;;;;;;;;
Hey!
-----------------------------------------------
Solution:
= (-18) - (4)
= -18 - 4
= -22
When you subtract a positive to a negative number the end result will always be negative.
-----------------------------------------------
Answer:
B. 22
-----------------------------------------------
Hope This Helped! Good Luck!
Distribute -3(40 - 2). -126 -114 126 114
Answer:
-114
Step-by-step explanation: I just did this
3y2 + 2xy + 1 + 3x + y + 2x2
Answer:
Simplified, it would be 2x^2+2xy+3y^2+3x+y+1 so that's your answer.
The given expression can not be simplified further.
The given expression is 3y² + 2xy + 1 + 3x + y + 2x².
What is an expression?In mathematics, an expression or mathematical expression is a finite combination of symbols that is well-formed according to rules that depend on the context.
Now, the given expression can not be simplified further.
The degree of the given expression 3y² + 2xy + 1 + 3x + y + 2x² is 2.
Here, the coefficient of y² is 3, the coefficient of xy is 2, the coefficient of x is 3, the coefficient of y is 1 and the coefficient of x² is 2.
Hence, the given expression can not be simplified further.
To learn more about the expression visit:
https://brainly.com/question/21751419.
#SPJ2
A few years ago. Sarah acquired a parcel of land valued at $16,500. Today, that same parcel of land has a value of $17.820. Find the percent increase in the property's
value. Round your answer to the nearest hundredth, if necessary.
Answer:
8%
Step-by-step explanation:
Use formula
[tex]\text{Percent increase}=\dfrac{\text{New value - Old value}}{\text{Old value}}\cdot 100\%[/tex]
Old value = $16,500
New value = $17,820
Hence, the percent increase is
[tex]\dfrac{\$17,820-\$16,500}{\$16,500}\cdot 100\%=\dfrac{\$1,320}{\$16,500}\cdot 100\%=\dfrac{8}{100}\cdot 100\%=8\%[/tex]
0.08 is equal to 8%, the percent increase in the value of the property is 8%.
First, calculate the increase in the value of the property:
increase = 17820 - 16500
= 1,320
Next, calculate the percent increase by dividing the amount of the increase by the original value of the property and multiply by 100%:
percent increase = (1320 / 16500) * 100
percent increase = 0.08
Since 0.08 is equal to 8%, the percent increase in the value of the property is 8%.
How is the graph of the parent function y=x^2 transformed to produce the graph of y=3(x+1)^2?
Answer:
Shift 1 units towards left and then stretch vertically 3 times.
Step-by-step explanation:
We are given that a parent function
[tex]y=x^2[/tex]
After transformation, we get a graph [tex]y=3(x+1)^2[/tex]
We have to find that how the parent function transformed to produce the graph of [tex]y=3(x+1)^2[/tex]
The parent graph is shifted 1 unit towards left by the rule of transformation
[tex]f(x)\rightarrow f(x+1)[/tex]
By applying this rule then, we get
[tex]y(x)=(x+1)^2[/tex]
Now, the parent function stretched vertically 3 times the previous graph by the rule
[tex]f(x)\rightarrow 3f(x)[/tex]
Apply this rule then, we get
[tex]y(x)=3(x+1)^2[/tex]
If y varies directly as x, and y is 180 when x is n and y is n when x is 5, what is the value of n?
18
Answer:
30
Step-by-step explanation:
y varies directly with x, so:
y = kx
When x = n, y = 180.
180 = kn
When x = 5, y = n.
n = 5k
Solve for k in the first equation:
k = 180 / n
Substitute into the second equation:
n = 5 (180 / n)
n = 900 / n
n² = 900
n = 30
Round the following numbers to 1 decimal place.
a)
27.564
b)
978.299
c)
42.935
d)
8.99
Answer:
a)27.6
b)978.3
c)43.0
d)9.0
IF YOU SOLVE FIRST YOU GET BRAINLIEST
Solve for x: 2/5(x − 2) = 4x. x = 2/9 x = −2 x = -2/9 x = -9/2
I solved 2/5(x − 2) = 4x. I don't know why you included those extra numbers.
-2/9
(R,2),(5,r),m=0 please solve
Answer:
r=2
Step-by-step explanation:
For aFor a beverage, Lisa mixes cups of lemonade to cups of iced tea in a ratio of 3:7. Which of the following best describes the amount of lemonade to iced tea? For every 3 cups of lemonade, there are 7 cups of iced tea. For every 3 cups of lemonade, there are 4 cups of iced tea. For every 7 cups of lemonade, there are 3 cups of iced tea For every 7 cups of lemonade, there are 4 cups of iced tea.
Answer:
A. For every 3 cups of lemonade, there are 7 cups of iced tea.
Step-by-step explanation:
The ratio is 3:7 and it stated that she mixed the lemonade cups with the iced tea. Therefore, A is the correct answer.
Answer:
3:7
Step-by-step explanation:
(2a+5b-7)+(a-9b-6) need help
Answer:
[tex]3a-4b-13[/tex]
Step-by-step explanation:
Given: [tex](2a+5b-7)+(a-9b-6)[/tex]
Since we are adding, there is no real use for the parenthesis. This may help you visualize it better.
[tex]2a+5b-7+a-9b-6[/tex]
Combine like terms:
[tex]3a-4b-13[/tex]
It is the answer shown below
3a-4b-13
Need help! what is 3√12 + √27 ?
Answer:
8√3
Step-by-step explanation:
3√12 = 3√4 x 3 = 5√3
√27 = 3√3
5√3 + 3√3 = 8√3
three times a certain number is 46 more than the number itself. Find the number.
Answer:
23
Step-by-step explanation:
3x=x+46
2x=46
x=23
23*3=69
23+46= 69
The number three times a certain number is 46 more than the number itself is 23.
What is mathematic expression?
A mathematical expression is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication, and division.
Let the number be x :
then, three times the number will be = 3x
46 more than the number itself will be = x+46
Now it is given that three times a certain number is 46 more than the number itself that is :
3x = x +46
3x-x = 46
2x = 46
x = 46/2
x =23
Therefore, the number three times a certain number is 46 more than the number itself is 23.
check and know more about equations here :
https://brainly.com/question/10003183
#SPJ2
calculate the exact value of
26.32+38.8/13.10- 11.56
Answer:
Step-by-step explanation:
28.32+38.8=65.12
13.10-11.6=1.56
65.12/1.56=41.7435897
ronald bikes 6.9 miles each day. How far has Ronald biked in seven days
Answer: 48.3 6.9 times seven
The distance biked in seven days is 48.3 miles.
Using the parameters given for our Calculation;
distance biked per day = 6.9 miles Number of days = 7To obtain the total amount of distance biked ;
Number of days * Distance biked per dayNow we have ;
6.9 * 7 = 48.3 milesHence, the distance biked is 48.3 miles .
Learn more on distance :https://brainly.com/question/28551043
#SPJ3
How to simplify 20/10
In order to get the answer to this question you will have to find the common factor and then divide the numerator and denominator by the common factor to get the answer.
[tex]\frac{20}{10}[/tex]
[tex]CF=10[/tex]
[tex]20\div10=2[/tex]
[tex]10\div10=1[/tex]
[tex]\frac{2}{1} =2[/tex]
[tex]= \frac{2}{1} or2[/tex]
Therefore the answer is "2."
Hope this helps.
At noon, a tank contained 8 cm of water. After several hours, it contained 4 cm of water. What is the percent decrease of water in the tank?
The water level in the tank decreased from 8 cm to 4 cm. This represents a decrease of 4 cm or a 50% decrease.
Explanation:The decrease in water level in the tank is calculated by finding the difference between the initial level and the final level. In this case, the initial level is 8 cm and the final level is 4 cm. The difference between these two levels is 4 cm.
To calculate the percent decrease, divide the decrease in level by the initial level and then multiply by 100%. So, in this case, the percent decrease in water level is (4 cm / 8 cm) * 100% = 50%.
The percent decrease of water in the tank from noon to several hours later is therefore 50%.
Learn more about Percent Decreasehttps://brainly.com/question/21285486?referrer=searchResults
#SPJ12
The percent decrease of water in the tank is 50%.
Explanation:To find the percent decrease of water in the tank, we need to calculate the difference in the water level and express it as a percentage of the initial water level.
The initial water level at noon is 8 cm and after several hours it decreases to 4 cm. The difference in water level is 8 cm - 4 cm = 4 cm.
To find the percentage decrease, divide the difference in water level by the initial water level and multiply by 100.
The percent decrease is (4 cm / 8 cm) * 100 = 50%.
Learn more about Percent decrease here:https://brainly.com/question/14808025
#SPJ12
Without graphing, classify each system as independent, dependent, or inconsistent
y = 4x+6
1-8x+2y=12
a. independent
b. dependent
c. inconsistent
please help
The system of equations provided is classified as inconsistent because the equations have equal slopes but different y-intercepts, indicating they are parallel lines without any intersection point.
Explanation:
To classify the system as independent, dependent, or inconsistent without graphing, we need to rearrange the equations into a common linear form, typically y = mx + b, where m is the slope and b is the y-intercept.
The given equations of the system are y = 4x + 6 and 1 - 8x + 2y = 12. Let's rewrite the second equation in the form y = mx + b, which results in y = 4x - 5.
Now, let's compare. The first equation has a slope of 4 (m1 = 4) and the second equation also has a slope of 4 (m2 = 4). However, the y-intercepts of the two lines (b1 = 6, b2 = -5) are different.
Since the slopes are equal and the y-intercepts are different, the system is inconsistent. In other words, the two lines are parallel and do not intersect, so there is no solution to the system.
Learn more about System of Linear Equations here:
https://brainly.com/question/20379472
#SPJ3
Please help! The following table shows the number of feet a helicopter flies above the ground as a function if time
Find and interpret the meaning of the x -interpret in this scenario
(10,0) the time it takes for the helicopter to reach the ground
(18,0) the time it takes the helicopter to take off
(10,0) the time it takes the helicopter to take off
(18,0) the time it takes for the helicopter to reach the ground
Answer:
18,0 the time it takes or the helicopter to reach the ground.
Step-by-step explanation:
if you look at the table, it slowly is decreasing, therefore it is going towards the ground.
Answer: The correct option is
(D) (18,0) the time it takes for the helicopter to reach the ground.
Step-by-step explanation: Given that the table shown in the picture gives the number of feet a helicopter flies above the ground as a function of time.
We are to find and interpret the meaning of the x -interpret in this scenario.
From the table, we note that
the graph of function f(x) will pass though the points (0, 18) and (2, 16).
So, the slope of the line graph of f(x) is
[tex]m=\dfrac{16-18}{2-0}=\dfrac{-2}{2}=-1[/tex]
Since the line passes through the point (0, 18), so its equation will be
[tex]y-18=m(x-0)\\\\\Rightarrow y-18=-1\timesx\\\\\Rightarrow y=-x+18.[/tex]
Now, to find x-intercept, we need to substitute y = 0 in the equation of the line.
So, at y = 0, we get
[tex]0=-x+18\\\\\Rightarrow x=18.[/tex]
Therefore, the required x-intercept is (18, 0) and is shows that the time taken by the helicopter to reach the ground is 18.
Thus, option (D) is CORRECT.
(-14) = ((-2) – (3 + (+2))] - 7
Help me
Answer:
The equation above has no question, but if there was, then yes, the equation above does equal -14
Step-by-step explanation:
Answer:
-14
Step-by-step explanation:
(−2) − (3+(2))−7
= - 2 - ( 3 + 2 ) - 7 = − 2 − ( 3 + 2 ) − 7
= - 2 - 5 - 7 = − 2 − 5 − 7
- 14
What is 6,000 using exponents
6,000 is [tex]6*10^3[/tex] in exponents.
Answer:
Step-by-step explanation:
shsjsjsj
What is 73.04 times 1.2
Answer:
87.648
this is the answer
Answer:
87.648 should be your answer